Dependency of Cholangiocarcinoma on Cyclin D–Dependent Kinase Activity - Gunya Sittithumcharee (2020)
© 2019 by the American Association for the Study of Liver Diseases. Cholangiocarcinoma (CCA) is a bile duct cancer with a very poor prognosis. Currently, there is no effective pharmacological treatment available for it. We showed that CCA ubiquitously relies on cyclin-dependent kinases 4 and 6 (CDK4/6) activity to proliferate. Primary CCA tissues express high levels of cyclin D1 and the specific marker of CDK4/6 activity, phospho-RB Ser780. Treatment of a 15-CCA cell line collection by pharmacological CDK4/6 inhibitors leads to reduced numbers of cells in the S-phase and senescence in most of the CCA cell lines. We found that expression of retinoblastoma protein (pRB) is required for activity of the CDK4/6 inhibitor, and that loss of pRB conferred CDK4/6 inhibitor-drug resistance. We also identified that sensitivity of CCA to CDK4/6 inhibition is associated with the activated KRAS signature. Effectiveness of CDK4/6 inhibition for CCA was confirmed in the three-dimensional spheroid-, xenograft-, and patient-derived xenograft models. Last, we identified a list of genes whose expressions can be used to predict response to the CDK4/6 inhibitor. Conclusion: We investigated a ubiquitous dependency of CCA on CDK4/6 activity and the universal response to CDK4/6 inhibition. We propose that the CDK4/6-pRB pathway is a suitable therapeutic target for CCA treatment.